2019
DOI: 10.3390/molecules24183343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Harvest Time on Phytochemical Constituents and Biological Activities of Panax ginseng Berry Extracts

Abstract: Ginseng (Panax ginseng) has long been used as a traditional medicine for the prevention and treatment of various diseases. Generally, the harvest time and age of ginseng have been regarded as important factors determining the efficacy of ginseng. However, most studies have mainly focused on the root of ginseng, while studies on other parts of ginseng such as its berry have been relatively limited. Thus, the aim of this study iss to determine effects of harvest time on yields, phenolics/ginsenosides contents, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As a result, the reducing power IC 50 of sea buckthorn berry was 15.095 µg/mL (Table 3). In addition, the result was somewhat higher than that of ginseng berries (11 µg/mL), known as representative antioxidant foods [22]. Here, we expected that this antioxidant activity of sea buckthorn berry is likely due to the presence of polyphenols that can act as free radicals scavengers by donating electrons or hydrogen.…”
Section: Reducing Powermentioning
confidence: 84%
“…As a result, the reducing power IC 50 of sea buckthorn berry was 15.095 µg/mL (Table 3). In addition, the result was somewhat higher than that of ginseng berries (11 µg/mL), known as representative antioxidant foods [22]. Here, we expected that this antioxidant activity of sea buckthorn berry is likely due to the presence of polyphenols that can act as free radicals scavengers by donating electrons or hydrogen.…”
Section: Reducing Powermentioning
confidence: 84%
“…GBJ was stored at −70 • C before the experiment. Biomarkers in GBJ were performed according to the previously reported method [12]. Cabbage (Brassica oleracea var.…”
Section: Plant Materials and Analytic Conditionsmentioning
confidence: 99%
“…The GB-related studies reported so far have clearly highlighted pharmacological activity, but studies for the application of preventive sources and functional food sources are poor. In a previous study, we reported the results of changes in physiological effects and biomarkers according to the optimal harvest time point of GB [12]. In this study, we removed the seeds of GB and prepared it as juice (GBJ).…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, the chemical composition of TCM is complex and exhibit large diferences in the types and quantities as afected by many factors, such as species, geographical regions, harvesting time, and processing conditions [41][42][43][44][45]. Tis would make it extremely difcult to understand the active compounds and the mechanism of TCM.…”
Section: Introductionmentioning
confidence: 99%